Qualitative systematic reviews and their role in evidence-based HIV nursing - Nalubega, Sylivia; Evans, Catrin (AUTUMN, 2014)
Decisions for healthcare delivery and health policies should be based on the highest level of existing research evidence.Achieving this can be challenging given the large body of existing literature generated by empirical studies, which may have biases, methodological flaws or may be time and/or context specific. Additionally, individual studies can reach conflicting conclusions making it hard to decide which results should inform policy or practice decisions. Systematic reviews, which bring together the results of primary studies, offer a solution to such concerns. Systematic reviews are described as explicit, reliable, reproducible scientific methods which limit bias by identifying, selecting, critically appraising and synthesising all literature on a given topic from all relevant individual studies. As such, they provide the most accurate and trustworthy results, which are more acceptable and accessible to decision-makers [3–6], enabling health care professionals to offer focused and individualised care, in which up-to-date evidence is integrated with patients’ own values and needs. There are many different types of systematic reviews. The most common are those based on quantitative evidence which may or may not include meta-analysis, and those based on qualitative evidence. This paper aims to describe the method and process of qualitative systematic reviews and their importance in informing evidence-based HIV nursing practice.